Effect of organic matters on anammox coupled denitrification system: when nitrite was sufficient. Issue 11 (13th November 2019) - Yang, Jingyue; Li, Jun; Zheng, Zhaoming; Hou, Liangang; Liang, Dongbo; Sun, Yiqi; Ma, Xiaoran
Abstract : Anaerobic ammonia oxidation (anammox) and denitrification can work together to weaken the influence of organic matter on anaerobic ammonia oxidation bacteria (AAOB) and improve nitrogen removal performance. As the common substrate of anammox and denitrification, nitrite will also affect nitrogen removal performance when it is insufficient, which is not conducive to reflect the endurance of anammox reactor to organic matter. The UASB continuous flow experiment was carried out to investigate the effect of the concentration of glucose and sodium acetate on nitrogen removal performance of anammox reactor under the condition of sufficient nitrite. With glucose as the organic matter, when the chemical oxygen demand (COD) concentration increased to 200 mg l −1, nitrogen removal performance of the system began to deteriorate significantly, and the anammox activity was significantly inhibited. With sodium acetate as the organic substance, the anammox activity was affected when the COD was 20 mg l −1 . Adequate nitrite could relieve the inhibition of the coupling system by a low concentration (COD < 200 mg l −1 ) of glucose organic matter. However, it could not relieve the inhibitory effect of sodium acetate. With the increase of organic concentration, the biological density of AAOB in granular sludge gradually decreased, while the biological density of denitrifying bacteria increased gradually.